Refining and conching alter the volatile composition of dark chocolate — Revealing profile changes in aroma-active volatiles and volatile organic compounds - Yvonne Guckenbiehl; Eva Ortner; Isabell Rothkopf; Andrea Buettner (Journal of Agriculture and Food Research)
The chocolate volatilome is formed by cocoa variety, growing region, and harvesting season but also by multiple post-harvest processes, namely fermentation, drying, roasting, and conching. To deepen the understanding of aroma changes during chocolate production, aroma-active volatiles and the profile of volatile organic compounds (VOCs) were investigated in cocoa liquor, both after refining in the so-called flakes, and in chocolate after conching. Aroma-active volatiles were analyzed applying gas chromatography-mass spectrometry/olfactometry combined with aroma extract dilution analysis and VOC profiles were screened by gas chromatography-ion mobility spectrometry. Overall, flavor dilution (FD) factors of up to 6 561, which refers to the maximum dilution of the distillates at which the odorants could be perceived, were determined, whereas dimethyl trisulphide, 2,3-diethyl-5-methylpyrazine, 3-(methylthio)propanal, 3-isobutyl-2-methoxypyrazine, 3-methylbutanoic acid, 4-hydroxy-2,5-dimethylfuran-3(2H)-one, γ-decalactone, 3-hydroxy-4,5-dimethylfuran-2(5H)-one, acetic acid, and 3-phenylpropanoic acid were among the aroma-active compounds eliciting the highest FD factors in the samples. Generally, the number of compounds detected, and the FD factors determined decreased along the processing steps, whereas FD factors of aldehydes partially increased as these are generated, inter alia, by lipid oxidation. The influence of processing was likewise mirrored in the VOC profile where conching in particular resulted in decreased VOC intensities. Individual VOC intensities, however, were increased after refining and conching, contributing to a discrimination of the different samples drawn after each processing step. Presumably, a major part of the VOCs detected in our study were not aroma-active. Our results thus provide an insight into the changes in volatile compounds’ composition during chocolate production and deliver a new perspective for monitoring the chocolate manufacturing process.